1996
DOI: 10.1073/pnas.93.22.12439
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of T-cell costimulation prevents development of experimental chronic renal allograft rejection.

Abstract: Blocking CD28-B7 T-cell costimulation by systemic administration of CTLA4Ig, a fusion protein which binds B7 molecules on the surface of antigen-presenting cells, prevents rejection and induces tolerance in experimental acute allograft rejection models. We tested the effect of CTLA4Ig therapy on the process of chronic renal allograft rejection using an established experimental transplantation model. F344 kidneys were transplanted orthotopically into bilaterally nephrectomized LEW recipients. Control These da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
86
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(89 citation statements)
references
References 26 publications
2
86
0
1
Order By: Relevance
“…21 Another study found that CsA did not abrogate renal allograft survival facilitated by CTLA4 immunoglobulin-mediated CD28/B7 blockade. 23 Our data indicate that CsA did not abrogate donor BM engraftment mediated by anti-CD40L mAb and, under some conditions, increased the proportion of recipients that engrafted ( Table 2, experiment 2). We hypothesize that CsA reduced the intensity of TCR signaling or clonally reduced the alloreactive T-cell population that may allow for a more readily attainable costimulatory blockade in a greater proportion of recipients.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…21 Another study found that CsA did not abrogate renal allograft survival facilitated by CTLA4 immunoglobulin-mediated CD28/B7 blockade. 23 Our data indicate that CsA did not abrogate donor BM engraftment mediated by anti-CD40L mAb and, under some conditions, increased the proportion of recipients that engrafted ( Table 2, experiment 2). We hypothesize that CsA reduced the intensity of TCR signaling or clonally reduced the alloreactive T-cell population that may allow for a more readily attainable costimulatory blockade in a greater proportion of recipients.…”
Section: Discussionmentioning
confidence: 75%
“…Literature reports have indicated that these immune suppressive agents can either inhibit or enhance solid organ graft acceptance when used in combination with costimulatory pathway blockade. 16,18,[20][21][22][23] In contrast to the restricted expression of alloantigen on a solid organ graft, alloantigenic targets of an immune response are widely distributed throughout the recipient or on donor BM cells that are systemically infused. In addition, patients are conditioned for BMT with chemotherapy and/or radiotherapy that can induce proinflammatory responses resulting in increased T-cell alloreactivity.…”
Section: Introductionmentioning
confidence: 99%
“…4 Although nonimmunologic factors may contribute to the immunopathological characteristics of CR, [75][76][77][78][79] evidence supporting a straightforword donor-specific HVG response as the core cause is overwhelming. [80][81][82][83][84] This pathogenesis explains very well why it has been so difficult in human organ recipients to achieve the closely related objectives of drug-free tolerance and freedom from CR. The prevention with immunosuppression of destructive immunity (i.e., rejection) for long enough to allow the variable induction of tolerance has been the sine qua non of clinical organ transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The sole possibility is to target nonimmune events, an option that works well in animals (7,18,19) but much less so in humans (20). Previous studies have found that systemic administration of the fusion protein CTLA4Ig or anti-CD28 mAb in addition to low-dose CsA to LW rat that received a Fisher kidney limited chronic rejection and prolonged survival (21)(22)(23). Inspired by these pivotal observations, we carried out this study using WF (RT1 u ) rats as donors and LW (RT1 l ) rats as recipients, which, being fully mismatched on both MHC class I and II antigens, could be representative of a broader range of clinical settings.…”
Section: Discussionmentioning
confidence: 99%